8x-(2x-3)=3(x-4)

Simple and best practice solution for 8x-(2x-3)=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(2x-3)=3(x-4) equation:


Simplifying
8x + -1(2x + -3) = 3(x + -4)

Reorder the terms:
8x + -1(-3 + 2x) = 3(x + -4)
8x + (-3 * -1 + 2x * -1) = 3(x + -4)
8x + (3 + -2x) = 3(x + -4)

Reorder the terms:
3 + 8x + -2x = 3(x + -4)

Combine like terms: 8x + -2x = 6x
3 + 6x = 3(x + -4)

Reorder the terms:
3 + 6x = 3(-4 + x)
3 + 6x = (-4 * 3 + x * 3)
3 + 6x = (-12 + 3x)

Solving
3 + 6x = -12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
3 + 6x + -3x = -12 + 3x + -3x

Combine like terms: 6x + -3x = 3x
3 + 3x = -12 + 3x + -3x

Combine like terms: 3x + -3x = 0
3 + 3x = -12 + 0
3 + 3x = -12

Add '-3' to each side of the equation.
3 + -3 + 3x = -12 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = -12 + -3
3x = -12 + -3

Combine like terms: -12 + -3 = -15
3x = -15

Divide each side by '3'.
x = -5

Simplifying
x = -5

See similar equations:

| 0.75-1/2(1/2-3) | | -4(p+9)=24.8 | | 7x-44=13+4x | | 2x-4+x+8=180 | | 6(x-5)=66/11 | | 11y*y= | | 6(6-5)=66/11 | | x+16=4x-7 | | 31=-.06m | | 29b^2+48-88b=0 | | Log[5](x-3)-log[5](x+4)=2 | | (6+3d)-3d=-10 | | 13(7x-8)=9x-6 | | 17x+48=180 | | -7(7x+5)-5= | | 31=-.06 | | 6(2v)= | | 3(4/9)-5y=1 | | (2/3)z=4(1/4) | | g(6)=-2x+4 | | 15x^2-12x-99=0 | | 11v+8=9v-18 | | 3a+4b=7b-a | | 17x+48=90 | | 4x^2+32x-64=0 | | 6=-7/2y | | 7a-4=4a+5 | | 4x^2+32-64=0 | | y/4=32 | | 23+30+x=90 | | 2(q-3)+6= | | 3-4(x+4)=6x-13 |

Equations solver categories